Computational analysis on thermal performance and coolant flow of an air-cooled polymer electrolyte membrane fuel cell / Wan Ahmad Najmi Wan Mohamed and Rahim Atan - Wan Mohamed, Wan Ahmad Najmi; Atan, Rahim (UiTM Press, 2010)
Polymer Electrolyte Membrane (PEM) fuel cells are electrochemical power generators that converts the energy potential of a hydrogen-based fuel into electricity with water and heat as the major by-products. The sensitivity of the solid polymer membrane to temperature requires that thermal management of a PEM fuel cell stack operates efficiently to maintain the temperature at the optimal level. Air cooling is normally applied for industrial PEM fuel cells of up to 2 kW power output. A computational investigation on the effective micro cooling channel geometries was conducted in order to enhance the practical capability of air cooling for a 3 kW stack power output with a reduced conversion efficiency of 30%. Plate and stack assembly simulation cases of a single channel and 40 cooling channel configurations using Computational Fluid Dynamics (CFD) were conducted with constant heat generation. The cooling performance was evaluated based on the boundary heat transfer and shows 100% effectiveness when subjected to airflows with a minimum Reynolds number of 200. The temperature distribution of the stack showed significant temperature gradients exists across the stack where multiple cooling channels provided a reduced gradient, approximately 50% less compared to the single channel. The coolant flow characteristics were also analyzed and an average velocity rise factor (AVRF) was introduced. Validation of the CFD simulation results was performed analytically and the simulation methodology reliability was found satisfactory by comparing the results of single plate simulations to the stack simulations